Fostering school reintegration after psychiatric inpatient treatment: description and study protocol of an evaluation study about a rehabilitation program for children and adolescents with chronic school refusal (SchuTIng-stAR) - Neumann, U.; Just, V.; Henke, L.; Knollmann, M.; Zellmer, S.; Andzinski, M.; Schmidtendorf, S.; Noack, M.; Föcker, M.; Seitz, J.; Holtmann, M. (Frontiers in Child and Adolescent Psychiatry, 2025)
BackgroundSchool refusal among children and adolescents with mental health issues carries long-term risks for their educational trajectories, future employment, mental health, and social participation. Despite the availability of multiple treatment approaches, a significant number of adolescents continue to experience difficulties with school attendance following inpatient therapy or partial hospitalization. To enhance reintegration into school, a rehabilitation project called “educational participation and integration for children and adolescents with mental illness through a seamless stepwise rehabilitation program” (“SchuTIng-stAR”) was developed specifically for children and adolescents with severe and persistent school refusal associated with psychiatric disorders who are at risk of continued school attendance problems after psychiatric inpatient treatment or partial hospitalization.Methods/study designAfter describing the therapeutic rationale, the development, and the content of the program, the study protocol for its evaluation using both quantitative and qualitative methods is presented. The primary objectives of the evaluation are firstly to assess the effects of the treatment on psychological symptoms and school attendance, and secondly to identify factors that influence the participation and engagement of patients, parents, and other stakeholders involved (teachers, youth welfare services). The operationalization of outcomes, measurement methods and hypotheses regarding effectiveness are described. Measurements will be taken at three points in time: at the beginning of the rehabilitation intervention (T1), at the end of treatment (T2) for the main outcome and after a six-month follow-up period (T3) for follow-up assessment. Therefore, it is a one-group pretest–posttest design with follow-up period. Additionally, it is explained how interviews with families will be analyzed using qualitative content analysis.DiscussionThe formative and summative evaluation of innovative treatment programs for children and adolescents, including the perspectives of relevant stakeholders, is essential to ensure their sustainability and their integration into already existing services provided by health and social care systems. As chronic school avoidance is a multifactorial and complex condition and its course is often characterized by relapses, it is important to develop sustainable treatment approaches and to closely examine treatment commitment using qualitative methods. The discussion focuses on the extent to which the rehabilitation intervention and the study produce the expected results, and what factors might contribute to divergent outcomes.